2017
DOI: 10.1016/j.jad.2017.06.066
|View full text |Cite
|
Sign up to set email alerts
|

White matter correlates of impaired attention control in major depressive disorder and healthy volunteers

Abstract: Background Major depressive disorder (MDD) is associated with impaired attention control and alterations in frontal-subcortical connectivity. We hypothesized that attention control as assessed by Stroop task interference depends on white matter integrity in fronto-cingulate regions and assessed this relationship using diffusion tensor imaging (DTI) in MDD and healthy volunteers (HV). Methods DTI images and Stroop task were acquired in 29 unmedicated MDD patients and 16 HVs, aged 18–65 years. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 96 publications
1
33
0
Order By: Relevance
“…The primary diffusion metrics (FA and MD) reflect overall white matter health, organization and maturation [ 36 ]. In addition, AD reflects axon integrity and RD reflects myelin sheath integrity [ 31 ]. Both AD and RD are of great significance in understanding the underlying physiological mechanism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary diffusion metrics (FA and MD) reflect overall white matter health, organization and maturation [ 36 ]. In addition, AD reflects axon integrity and RD reflects myelin sheath integrity [ 31 ]. Both AD and RD are of great significance in understanding the underlying physiological mechanism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…All participating individuals provided informed consent for the study, following explanation of the experimental procedures of the study. reported in an analysis of suicide attempters (Olvet et al, 2014) and impaired attention in MDD (Rizk et al, 2017).…”
Section: Subjectsmentioning
confidence: 95%
“…The dMRI data from 20 of these subjects was previously reported in an analysis of suicide attempters (Olvet et al, 2014) and impaired attention in MDD (Rizk et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Many studies of MDD have shown significant differences in FA between MDD and non-MDD patients 17 , 18 , 20 , 25 , 28 , 29 . Recently, the largest multi-site DTI study in MDD showed evidence for global differences in FA and radial diffusivity in multiple WM, including the corpus callosum, internal capsule, corona radiata, cingulum, and fornix, in MDD 48 .…”
Section: Discussionmentioning
confidence: 99%
“…This technique represents a promising approach for early diagnosis of various neurodegenerative diseases 16 . Although many studies have evaluated MDD using DTI 17 30 , few studies have used DKI 31 , 32 . In those studies, the DKI showed a decrease in the mean kurtosis (MK) and radial kurtosis values, which were specific parameters that could not be expressed by DTI, in a wider range than that of fractional anisotropy (FA) value decreased.…”
Section: Introductionmentioning
confidence: 99%